1993
DOI: 10.2307/3578353
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Receptor Binding of Cisplatin and Terbium in Human Breast Tumor Cells after Hyperthermia

Abstract: Terbium phosphorescence was used to investigate a thermosensitive calcium binding protein located in the plasma membrane of human MCF-7 breast tumor cells. The cells were pretreated at 25, 37, or 43 degrees C for 1 h, before binding experiments were performed at 25 degrees C. The delta Imax for the Tb(3+)-MCF/7 complex increased significantly after cellular exposure to 43 degrees C. The Kd for the Tb(3+)-MCF/7 complex did not change with the temperature. These results suggested that hyperthermia can unmask pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
5
0
2
Order By: Relevance
“…In addition, 90Y is easily separated by column chromatography from 90Sr, which has a very long half-life (28.8 years). It has been shown that Tm3+, Tb3+, and Yb3+ have a high affinity for tumor cells (24)(25)(26)(27). It is interesting to note that Tb3+ was temperature-dependently taken up by tumor cells (MCF-7), and cisplatin, a well-known anticancer drug, reduced the binding of Tb3+ to those tumor cells (25).…”
Section: Exposure To Rare Earthsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 90Y is easily separated by column chromatography from 90Sr, which has a very long half-life (28.8 years). It has been shown that Tm3+, Tb3+, and Yb3+ have a high affinity for tumor cells (24)(25)(26)(27). It is interesting to note that Tb3+ was temperature-dependently taken up by tumor cells (MCF-7), and cisplatin, a well-known anticancer drug, reduced the binding of Tb3+ to those tumor cells (25).…”
Section: Exposure To Rare Earthsmentioning
confidence: 99%
“…It has been shown that Tm3+, Tb3+, and Yb3+ have a high affinity for tumor cells (24)(25)(26)(27). It is interesting to note that Tb3+ was temperature-dependently taken up by tumor cells (MCF-7), and cisplatin, a well-known anticancer drug, reduced the binding of Tb3+ to those tumor cells (25). However, there is a contradictory report that has shown that La concentration in malignant laryngeal tissue was lower than in nonmalignant adjacent tissues, although serum La concentrations of laryngeal cancer patients were significantly higher than those of normal subjects (28).…”
Section: Exposure To Rare Earthsmentioning
confidence: 99%
“…The Yb 3+ -transferrin complex inhibited the uptake of the fluorescein labeled ferric-saturated transferrin (Fe 2 -transferrin) complex into K562 cells. The results demonstrate that the complex of Yb 3+ -transferrin complex was recognized by the transferrin receptor and that the transferrin-receptor-mediated mechanism is a possible pathway for Yb 3+ accumulation in cells.Keywords: K562 cells; recognition; transferrin; ytterbium.Lanthanides have been suggested for the treatment of a series of diseases and for diagnosis by magnetic resonance imaging [1,2]. Recent studies also show that they could act as scavengers of free radicals [3] and therefore protect cells and tissues from oxidative stress-induced injury.…”
mentioning
confidence: 99%
“…Lanthanides have been suggested for the treatment of a series of diseases and for diagnosis by magnetic resonance imaging [1,2]. Recent studies also show that they could act as scavengers of free radicals [3] and therefore protect cells and tissues from oxidative stress-induced injury.…”
mentioning
confidence: 99%
“…Além das diversas aplicações descritas anteriormente, terras raras há muito tempo têm sido investigados para o tratamento de doenças e para diagnóstico por imagem na técnica de ressonância magnética 6,7 . Estudos mais recentes mostram que poderiam agir como capturadores de radicais livres e, portanto proteger células e tecidos de dano induzido por fadiga oxidativa, com potenciais ações farmacológicas 8 .…”
Section: Segundo O Centro De Gestão E Estudos Estratégicosunclassified